2011
DOI: 10.1111/j.1542-4758.2011.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of free light chain hemodialysis in myeloma cast nephropathy: A case–control study

Abstract: New very high permeability dialysis membranes have been developed to enable the clearance of free light chains in myeloma cast nephropathy. These new dialysis techniques, in combination with chemotherapy, should allow improved prognosis in patients with myeloma cast nephropathy. We report a prospective observational study comparing patients who underwent hemodialysis in our center in 2009 for cast nephropathy revealing multiple myeloma vs. patients treated for the same condition during the same period in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
(70 reference statements)
3
18
0
Order By: Relevance
“…Since 2007, there has been a focus on high cutoff haemodialysis (HCO-HD) for removal of sFLC; HCO-HD relies on use of a highly permeable dialysis membrane that is very effective in clearing both FLC isotypes 17 and is more effective than plasma exchange because it can be used for longer treatment sessions. 18 Uncontrolled clinical trials 11,[19][20][21] have shown a high frequency of renal recovery in patients who were dialysis-dependent and received HCO-HD. However, the effect of novel chemotherapy was not evaluated in these studies, and a 2017 randomised controlled trial, 22 in which all patients received a multiple myeloma treatment containing bortezomib and dexamethasone, showed no differences in the primary outcome of independence from dialysis at 90 days between the group randomly assigned to receive HCO-HD and the group randomly assigned to receive high-flux haemodialysis (HF-HD), although increased overall renal recovery was reported in patients who received HCO-HD.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, there has been a focus on high cutoff haemodialysis (HCO-HD) for removal of sFLC; HCO-HD relies on use of a highly permeable dialysis membrane that is very effective in clearing both FLC isotypes 17 and is more effective than plasma exchange because it can be used for longer treatment sessions. 18 Uncontrolled clinical trials 11,[19][20][21] have shown a high frequency of renal recovery in patients who were dialysis-dependent and received HCO-HD. However, the effect of novel chemotherapy was not evaluated in these studies, and a 2017 randomised controlled trial, 22 in which all patients received a multiple myeloma treatment containing bortezomib and dexamethasone, showed no differences in the primary outcome of independence from dialysis at 90 days between the group randomly assigned to receive HCO-HD and the group randomly assigned to receive high-flux haemodialysis (HF-HD), although increased overall renal recovery was reported in patients who received HCO-HD.…”
Section: Introductionmentioning
confidence: 99%
“…Renal recovery was correlated with improved survival. One small case control study has also shown improved rates of renal recovery and dialysis discontinuation with HCO hemodialysis (40). The promising benefits of HCO hemodialysis are being tested combined with bortezomib-based chemotherapy in the multicenter RCT European Trial of Free Light Chain Removal by Extended Hemodialysis in Cast Nephropathy.…”
Section: Intrinsic Causesmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] It was first reported to treat CN caused by MM in 2007 by Hutchison et al 8 Afterwards, the same unit has performed series researches to study the factors affecting clearance in HCO-HD and the relationship between the removal of FLC by HCO-HD and clinical outcomes. 13,18,19 However, what is proved critically important for reduction of blood FLC and improvement of outcome in these noncontrol studies is effective chemotherapy; the role of HCO-HD in these issues is still waiting to be confirmed by the results of the ongoing randomized control trial. 13,18,19 However, what is proved critically important for reduction of blood FLC and improvement of outcome in these noncontrol studies is effective chemotherapy; the role of HCO-HD in these issues is still waiting to be confirmed by the results of the ongoing randomized control trial.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,17 The preliminary results showed that early HCO-HD combined with chemotherapy may contribute to improvement of renal function in patients with MM-caused CN through decreasing blood FLC concentration. 13,18,19 However, what is proved critically important for reduction of blood FLC and improvement of outcome in these noncontrol studies is effective chemotherapy; the role of HCO-HD in these issues is still waiting to be confirmed by the results of the ongoing randomized control trial. 17 Our experience for HCO-HD in one case showed HCO-HD combined with chemotherapy greatly decreased The clearance of FLC l measured in this patient was 38.4 mL/min at the start of HD, which is higher than that reported by Hutchison et al using one HCO1100 filter (surface area 1.1 m 2 ) and is comparable with that using two HCO1100 filters in series.…”
Section: Discussionmentioning
confidence: 99%